DETERMINATION OF MACRO-MICRO NUTRIENT CONTENTS IN DRIED FRUIT AND LEAVES AND SOME POMOLOGICAL CHARACTERISTICS OF SELECTED FEIJOA GENOTYPES (Feijoa sellowiana Berg.) FROM SAKARYA PROVINCES IN TURKEY - O. Beyhan; M. A. Bozkurt; S. C.Boysal (Journal of Animal and Plant Sciences, 2011)
This study was conducted to determine some pomological characteristics and macro- micro nutrient contents of both leaves and fruits of 11 Feijoa genotypes (Feijoa sellowiana Berg.) selected from Sakarya Province in Turkey. For these genotypes, fruit weight, fruit length, fruit width, soluble solid content and fruit acidity values ranged between 18.57 – 40.00 g, 27.74 -59.95 mm, and 23.42-39.43 mm, 8.30-14.20%, and 3.33-4.50, respectively. The analysis results showed that N, P, K, Ca, Mg, Fe, Mn, Zn, and Cu contents in dried fruits of these selected genotypes were 0.72-1.47%, 0.091-0.104%, 0.53-0.94%, 0.33-0.75%, 0.070-0.103%, 38-200 ppm, 2.10-6.30 ppm, 2.90-7.30 ppm, and 1.71- 6.95 ppm. On the other hand, N, P, K, Ca, Mg, Fe, Mn, Zn, and Cu contents of leaves for those contents were 1.42-2.31%,0.092-0.134%, 0.32-0.66%, 1.70-3.40%, 0.19-0.32%, 70-148 ppm,18-63 ppm, 6.70-11.10 ppm, and 1.32- 2.88 ppm. Significant differences among these genotypes were found for chemical composition (P<0.05). As all the trees were in similar environment and agronomical practices, it could be suggested that these differences due to genotypic differences.
Keywords: Feijoa; Acca sellowiana; Selection; Chemical content.